2011
DOI: 10.1002/asna.201011485
|View full text |Cite
|
Sign up to set email alerts
|

The solar photospheric abundance of zirconium

Abstract: Zirconium (Zr), together with strontium and yttrium, is an important element in the understanding of the Galactic nucleosynthesis. In fact, the triad Sr-Y-Zr constitutes the first peak of s-process elements. Despite its general relevance not many studies of the solar abundance of Zr were conducted. We derive the zirconium abundance in the solar photosphere with the same CO 5 BOLD hydrodynamical model of the solar atmosphere that we previously used to investigate the abundances of C-N-O. We review the zirconium… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 34 publications
(79 reference statements)
0
16
0
Order By: Relevance
“…A comparison of FUNS predictions on stellar masses and cluster ages with the values derived by Gilroy (1989) showed good agreement within the uncertainties, so we refrained from re-determining the stellar masses of our sample stars. We point out that there is a minor inconsistency in our study in the sense that the oxygen abundance given by Lodders et al (2009) is 0.07 dex lower than the value of Caffau et al (2009) we used for computing the model spectra. Since the difference is very small, this inconsistency has negligible consequences on our analysis.…”
Section: Nucleosynthesis and Mixing Modelsmentioning
confidence: 71%
“…A comparison of FUNS predictions on stellar masses and cluster ages with the values derived by Gilroy (1989) showed good agreement within the uncertainties, so we refrained from re-determining the stellar masses of our sample stars. We point out that there is a minor inconsistency in our study in the sense that the oxygen abundance given by Lodders et al (2009) is 0.07 dex lower than the value of Caffau et al (2009) we used for computing the model spectra. Since the difference is very small, this inconsistency has negligible consequences on our analysis.…”
Section: Nucleosynthesis and Mixing Modelsmentioning
confidence: 71%
“…A less "anemic" Sun would better agree with new, accurate determinations of the solar Si content accounting for non-LTE effects ). Both of these changes, together with hints that 3D-based revisions in other chemical elements may seemingly not need to be drastic compared to the 1D case (e.g., see the results of Caffau et al 2009, based on CO 5 BOLD 3D granulation models), should help alleviate the discomfort that helioseismology has been feeling towards low values of the solar metal content. In any case, it will be very interesting to investigate how 3D, non-LTE, and magnetic effects interact, and whether there may be some amplification or reduction in their magnitude when looking at a fully consistent picture in order to carry out an absolute abundance determination.…”
Section: Discussionmentioning
confidence: 99%
“…Among other open questions, the most critical and urgent are (i) the friction with helioseismic inversion constraints (Antia & Basu 2005;Delahaye & Pinsonneault 2006) caused by the up to ∼30% smaller estimate currently widely adopted for the solar photospheric metal content; (ii) several authors (e.g., Caffau et al 2007Caffau et al , 2008Caffau et al , 2010Caffau et al , 2011Ayres 2007Ayres , 2008 have suggested that the revision in the abundance of a number of chemical elements may be too drastic, for example due to slightly too steep temperature gradients in the employed models' continuumforming layers (Trujillo Bueno & Shchukina 2009) or too low temperatures in their middle photospheric layers (Ayres 2012); (iii) Caffau et al (2009) claim that the revised solar abundances are likely to be mostly an outcome of differences in equivalent width and/or in line profile fitting, as well as in blend treatment and in atomic data, with granulation effects and hydrodynamical modelling playing a less important role.…”
Section: Introductionmentioning
confidence: 99%
“…It also overlaps the meteoritic value (log Zr = 2.53 ± 0.04; Lodders et al 2009) to within the mutual uncertainties. Caffau et al (2011a) recently redetermined the solar abundance of Zr using their 3D model. Their 3D LTE result, log Zr = 2.62 ± 0.06, from a sample of 15 Zr  lines, is slightly larger than ours.…”
Section: Zirconiummentioning
confidence: 99%
“…Previous papers in this series have focussed on Na -Ca (Scott et al 2014a: Paper I) and the Fe group (Scott et al 2014b: Paper II) with remaining elements to be dealt with in future studies. Amongst the heavy elements, so far zirconium Caffau et al 2011a), osmium (Caffau et al 2011b), europium (Mucciarelli et al 2008), hafnium and thorium ) have been subjected to 3D solar analysis.…”
Section: Introductionmentioning
confidence: 99%